Greenway Cyclists’ Visual Perception and Landscape Imagery Assessment - He, Hui; Li, Jiamin; Lin, Xiaowu; Yu, Yanwei (Frontiers in Psychology, 2021)
Greenway is a kind of corridors in the city that takes natural elements as the main constituent foundation and connects open spaces with functions such as leisure and recreation. The assessment of the built greenway is a review of the past construction experiences, and it is also a supplement and improvement to the future greenway planning concept system, which has important academic and application value. This study will explore how greenway design factors influenced the local cyclists' perception of the landscape using on-site questionnaire and photo rating method. The results indicated that greenways with continuous cycling paths, high security awareness, open landscapes, and rich human activities evoke positive perceptions. Among the visual elements, natural elements such as plants and sky are more favorable than artificial elements. The research results show that the formation of greenway cyclists' landscape imagery is affected by visual perception elements, which suggests that special consideration should be given to the laws of cyclists’ mental perception when designing greenways.